Human Rights Protection in the Era of Artificial Intelligence: A Comparative Legal Analysis of Ethical Governance and Regulatory Frameworks - Rengga Kusuma Putra; Lita Tyesta Addy Listya Wardhani; Edvardas Juchnevicius; Sandra Leoni (International Forum of Researchers and Lecturers, 2025)
The rapid advancement and integration of Artificial Intelligence (AI) into diverse sectors of society have generated complex ethical and human rights challenges. Technologies involving surveillance, data collection, algorithmic decision-making, and facial recognition pose significant risks to privacy, equality, and freedom of expression. This study examines the intersection of AI and human rights through a comparative analysis of regulatory frameworks in the European Union (EU), the United States (US), and Asia. Employing a comparative legal approach, the research analyzes international and national regulatory instruments, including the EU AI Act, the General Data Protection Regulation (GDPR), and China’s Personal Information Protection Law (PIPL). Case studies of AI-related human rights violations, such as algorithmic bias and discrimination, are incorporated to illustrate real-world implications. Findings reveal substantial differences in governance approaches: the EU emphasizes a risk-based model prioritizing human rights protections, while the US and Asia adopt more fragmented or centralized strategies. The study underscores the urgent need for global regulatory harmonization to safeguard fundamental rights and promote ethical AI development. By highlighting both strengths and limitations of existing frameworks, the research contributes to ongoing debates on balancing innovation with accountability, transparency, and human rights protection in the digital era.